Duration & Dimension - Winfried G. Hallerbach (Tinbergen Institute, 1999)
In fixed income analysis, duration plays a central role as a proxy for interestrate risk exposure. Althoughthis role relies on the interpretation of duration as (minus) theyield elasticity of the bond price, duration ismeasured as a bond's present value weighted average time to maturity andexpressed in terms of years. Hence duration is regarded as an elasticity with a time dimension. Inthis note we resolve this apparentduration paradox and show that duration is a pure number.
Keywords: 330; Anleihe; Zins; Dauer; Theorie